Research progress on the application of nanoparticles delivery in the treatment of atherosclerosis: implications for therapeutic interventions - Hao, Menglei; Wang, Yaoling; Zhang, Shaomin; Yu, Shuaishuai; Mo, Chunheng; Wu, Jinhui (Frontiers in Cell and Developmental Biology, 2025)
Atherosclerosis (AS) is a chronic cardiovascular disease and a leading cause of global morbidity and mortality. Its pathological features include lipid accumulation within the arterial walls, macrophage infiltration, and the proliferation of fibrous plaques, which can manifest in various blood vessels throughout the body. The dislodgement of arterial plaques can lead to severe complications, such as myocardial and cerebral infarction. Current therapeutic strategies for AS focused on managing risk factors, including hypertension, and dyslipidemia. However, the adverse effects of medications and the progression of plaques remain challenges. Nanoparticles (NPs), defined as naturally occurring or biosynthesized particles with immunomodulatory properties and sizes ranging from 1 nm to 100 nm, represent a novel drug delivery system. This technology enhances drug stability and targeting specificity while reducing off-target toxicity. NPs encapsulating therapeutic agents or gene-editing components are capable of facilitating transmembrane transport and cross-barrier release, effectively targeting AS plaques to modulate the activity of macrophages and endothelial cells. This mechanism aids in the treatment of plaques and subsequently reduces complications. The advancement of NPs delivery technology offers extensive potential for AS-targeted therapies and personalized medicine. This review aims to summarize recent advances in NP-based delivery systems for AS treatment.